(untitled) (Tanzania Medical Journal, 2021)
Introduction Congenital tuberculosis (TB) which is acquired during the intrauterine period or during the normal birth process is rare, with 490 cases reported up to date. Congenital Tuberculosis poses a diagnostic challenge because its clinical presentation and radiographic findings are nonspecific. Case Presentation We present an African neonate born prematurely at gestation age of 32 weeks, weighing 1250 grams at Muhimbili National Hospital. The mother was admitted at the Intensive Care Unit (ICU) before delivery due to empyema thoracis and later on died. She was HIV negative, later on diagnosed with TB and initiated on anti –Tb medications 3 days before her demise which was two weeks post-delivery. The baby who was never breastfed, presented with a history of poor weight gain, persistent fever, cough and difficulty in breathing during the neonatal period. On physical examination she had reduced breath sounds on the right side of the chest and hepatosplenomegaly. Gastric aspirate for Gene Xpert confirmed the presence of Mycobacterium tuberculosis. The patient was initiated on anti –Tb medication and responded well with adequate weight gain and improvement of the clinical symptoms. Conclusion A high index of suspicion is required to diagnose congenital TB, in light of poor response to antibiotics in TB endemic areas, especially when the mother is presenting with respiratory symptoms.